IMPROVING STUDENT'S NATURALIST INTELLIGENCE THROUGH OUTDOOR ACTIVITIES ON PLANT MORPHOLOGY LEARNING - Lismaya, Lilis (Universitas Kuningan, 2018)
The purpose of this research is to analyze the improvement of students' naturalist intelligence through outdoor activities on plant morphology learning, to analyze the difference of result between pre test and post test on plant morphology learning, and to reveal students’ response to the application of plant morphology learning. The research method used is a weak experimental research design with the one-group pretest-posttest design. This study used only one experimental class given treatment to assess the effect of the treatment, without comparison with the control class. The instrument used is questions of naturalist intelligence. The results of this research are: 1) There is a difference of result between pre test and post test on student's naturalist intelligence before and after plant morphology learning using outdor activities; 2) There is improvement of students' naturalist intelligence through outdoor activities learning; 3) Positive response came from students on the application of outdoor activites learning.Keywords: naturalist intelligence; outdoor activities; plant morphology.